Rancangan API Interoperabilitas Monitoring dan Pelaporan Standar Pelayanan Minimal Bidang Kesehatan Kabupaten Cilacap - Farid Mahmudi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2023)
The Minimum Service Standards for the Health Sector (SPM-BK) at Cilacap District in 2019 and 2020 showed that no type of basic service has reached the target. This has decreased compared to 2018 where health services at the age of basic education can meet standards. Interoperability is important to integrate SPM data from all health facilities so that data can be accessed easily, quickly and accurately. This study aims to analyze and design the interoperability of information system data in health facilities for reporting SPM-BK. This type of research is operational research using qualitative methods. Data collection was carried out by interviewing and observing user needs (planning and analysis stages), making system architectural designs (design stages), as well as system trials. The results of the in-depth interviews were analyzed using the content analysis method. Evaluation of the system used is carried out descriptive analysis as a basis for analysis of interoperability systems for monitoring SPM-BK data. This research produces an interoperability system that facilitates the process of transferring data so that information can be obtained quickly and accurately. The development of interoperability to help manage data and information still has the potential to be carried out. Development of SPM-BK system interoperability can facilitate reporting. Data information can be easily seen and found and data security can be guaranteed.